2010
DOI: 10.1021/ic902430w
|View full text |Cite
|
Sign up to set email alerts
|

Solution Synthesis and Characterization of Indium−Zinc Formate Precursors for Transparent Conducting Oxides

Abstract: A series of In-Zn formate mixtures were investigated as potential precursors to amorphous In-Zn-oxide (IZO) for transparent conducting oxide (TCO) applications. These mixtures were prepared by neutralization from formic acid and characterized by elemental analysis, IR spectroscopy, powder X-ray diffraction, and thermogravimetry-differential scanning calorimetry (TG-DSC) measurements. Thermal analysis revealed that a mixture of In and Zn formates reduced the overall decomposition temperature compared to the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Pasquarelli et al have demonstrated amorphous/nanocrystalline IZO films prepared by ultrasonic spray deposition from formate precursors with annealing at 300-400 1C. 106,264 Solutions consisted of In(HCOO) 2 (OH) and Zn(HCOO) 2 Á2H 2 O in a methanol-water-acid (6 : 1 : 0.2 vol) mixture. Films were amorphous at indium contents as low as 40 at% but with low conductivities of o50 S cm À1 .…”
Section: Sno 2 :(Fsbmentioning
confidence: 99%
“…Pasquarelli et al have demonstrated amorphous/nanocrystalline IZO films prepared by ultrasonic spray deposition from formate precursors with annealing at 300-400 1C. 106,264 Solutions consisted of In(HCOO) 2 (OH) and Zn(HCOO) 2 Á2H 2 O in a methanol-water-acid (6 : 1 : 0.2 vol) mixture. Films were amorphous at indium contents as low as 40 at% but with low conductivities of o50 S cm À1 .…”
Section: Sno 2 :(Fsbmentioning
confidence: 99%
“…Black powders have been observed during the decomposition of indium formate precursors and was attributed to the presence of metallic indium using XRD. 22 However, no metallic indium was detected by XRD in the black material from In 5 O(OPr i ) 13 . This would suggest that the black-to-yellow color transition is instead the result of a conversion from a substoichiometric oxide to a more stoichiometric oxide with temperature.…”
Section: Precursor Decompositionmentioning
confidence: 98%
“…The sintered nickel nanoparticle inks can obtain an electrical resistivity ranging from 20 to 50 µΩ cm, which are applicable for fabricating conductive tracks and patterns. Pasquarelli et al also reported depositing nickel nanoparticle inks onto glass and zinc oxide with an inkjet printer to fabricate electrode contacts for solar cell applications. Possible applications with nickel nanoparticle inks may include temperature sensors, inductors and microheaters.…”
Section: Single Element Metallic Nanoparticle Inksmentioning
confidence: 99%